2013
DOI: 10.1007/s10329-013-0385-z
|View full text |Cite
|
Sign up to set email alerts
|

Niche separation of sympatric macaques, Macaca assamensis and M. mulatta, in limestone habitats of Nonggang, China

Abstract: Comparative studies of sympatric species are essential in understanding those species' behavioral and ecological adaptations as well as the mechanisms that can reduce resource competition enough to allow coexistence. We collected data on diet, activity budget and habitat use from two sympatric macaque species, the Assamese macaque (Macaca assamensis) and the rhesus macaque (M. mulatta), in a limestone seasonal rainforest of Nonggang Nature Reserve, southwestern Guangxi, China. Our results show that the two sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
2
24
3
Order By: Relevance
“…Rhesus macaques were dependent on more plant species than were Assamese macaques. Of the two major dietary components, plants and insects, Assamese macaques were predominantly folivores, as reported in previous studies (Justa et al 2019;Zhou et al 2014Zhou et al , 2018, followed by frugivory. Insects were another major dietary component for Assamese macaques, compared to rhesus macaques.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Rhesus macaques were dependent on more plant species than were Assamese macaques. Of the two major dietary components, plants and insects, Assamese macaques were predominantly folivores, as reported in previous studies (Justa et al 2019;Zhou et al 2014Zhou et al , 2018, followed by frugivory. Insects were another major dietary component for Assamese macaques, compared to rhesus macaques.…”
Section: Discussionsupporting
confidence: 79%
“…Chalise (2003) and Huang et al (2015) reported that Assamese macaques preferred flowers and fruits when their availability was dominant; nonetheless, these findings conflict with those of the present study and most previous studies. Feeding preferences of rhesus macaques in the present study included leaves, as reported by Goldstein and Richard (1989) and Tang et al (2016), but unlike most findings on frugivory (Schülke et al 2011;Zhou et al 2014;Justa et al 2019;Feeroz 2011). Nevertheless, without phenological information on food availability and distribution, our study cannot reliably address the factors of seasonality in their activity patterns, because fruit consumption is influenced by availability (Sengupta and Radhakrishna 2016) and activities are shaped by the environmental and physiological systems of the species (Ruslin et al 2019).…”
Section: Discussioncontrasting
confidence: 51%
“…Climbing might also minimise path length and thus save energy [Huang et al, 2015]. Like François' langurs, sympatric Assamese macaques also spend much of their time on cliffs and choose ledges and caves as sleeping sites [Zhou et al, 2014], and climbing is their most common locomotor mode [Huang et al, 2015].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…During dry months, sitting together in huddles to conserve energy could be an effective adaptation for lowering temperatures. In fact, behavioural thermoregulation occurs in sympatric primates, including white-headed langurs (Trachypithecus leucocephalus) and Assamese macaques, which sun-bathe in winter and rest in the shade or in caves in summer [Huang, 2002;Zhou et al, 2014]. A detailed study on thermoregulation in Francois' langurs is needed.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The sample size seen in Table 5 M. mulatta, given it is the most widely distributed and successful primate. However, M. mulatta is always reported as occurring at lower elevation compared with its sympatric primates (Coudrat & Nekaris, 2013;Huang et al, 2015;Molur et al, 2003;Zhou et al, 2014), whereas M. leonina usually occurs over a wider range of elevations (Choudhury, 2010;Islam et al, 2014;Nguyen et al, 2012;San, 2011;Yin, 1993). With space more limited in the overlapping area, the niche of M. leonina narrowed in the vegetation dimension, F I G U R E 4 Differentiation between two macaque species in their overlapping area, by elevation (a), vegetation (b) and activity pattern (c) in three seasons: dry-cool (column 1), dry-hot (column 2), and rainy (column 3).…”
Section: Wider Distribution and Niche Breadth Of M Leoninamentioning
confidence: 99%